Non-coding RNAs: Emerging Functions and Implications in Cervical Cancer - Pratap, Pushpendra D.; Raza, Syed Tasleem; Ahmad, Sharique; Wasim, Saeeda (Cutting Edge Research in Biology Vol. 4, 2023)
CC represents the most common tumour in females globally, notwithstanding the potential for prevention through the implementation of recognised therapies, such as preemptive immunization, comprehensive disease screening, and therapy. The prognosis for entities with advanced or metastatic CC is quite deprived, and there are currently very few effective treatment approaches. Establishing new therapeutic goals and comprehending the mechanism of metastasis are essential. A comprehensive representation of the structure of the human transcriptome has been made possible by new sequencing technologies. By forming associations with DNA, RNA, and even proteins, ncRNAs make a wide range of contributions in transcriptional, translational, and post-translational processes. Emerging studies have revealed that ncRNAs have a significant regulatory role in a number of biological functions, with the expression of these molecules strictly regulated in physiological conditions. Extensive work has been devoted to examining the relevance of ncRNAs in a diverse range of human disorders, especially carcinoma, throughout recent times, primarily during the last decade. As a result, focusing on the roles of ncRNAs may aid in our understanding of CC. Throughout this chapter, we aimed to demonstrate the newly discovered functions of ncRNAs in CC development, invasion, treatments, chemo-resistance, HPV modulation, biochemical remodeling, diagnostics, as well as a prognostic biomarker.